The South Indian Pentecostal movement in the twentieth century - Bergunder, Michael (Eerdmans, 2008)
Early Beginnings -- Kerala -- Tamil Nadu -- Karnataka -- Andhra Pradesh -- Evangelists, Interchurch fellowships, and marginal movements -- Context -- Themes -- Ordo Salutis -- Gifts of the Spirit -- Ethics -- Ministry -- Church Life -- Social Structure and Ecumenical Relations -- Pentecostalism and Contextualization of Christianity -- Selected Biographies -- Missionaries and Leadership Positions -- Church Statistics
Literaturverz. S. 321 - 356
Keywords: India, South -- Church history -- 20th century; Geschichte; Pfingstbewegung; Indien